OnabotulinumtoxinA for the treatment of overactive bladder - Cox L; Cameron AP (Research and Reports in Urology, 2014)
Lindsey Cox, Anne P Cameron Department of Urology, University of Michigan, Ann Arbor, MI, USA Abstract: OnabotulinumtoxinA injection is a safe and effective treatment for adults with refractory overactive bladder. There is sufficient level 1 evidence to support offering onabotulinumtoxinA injections as a second-line treatment to patients who have failed behavioral therapy and oral medications such as antimuscarinics and β3 agonists. An intradetrusor injection of 100 U of onabotulinumtoxinA is likely the optimal dose to balance risks and benefits, and this is the dose approved by the US Food and Drug Administration. Improvement in urgency urinary incontinence episodes, as well as symptom scores and quality of life, were seen in around 60%–65% of patients, and were significantly improved compared with those on placebo. Most studies have reported a duration of symptom relief ranging from 6 to 12 months, with repeat injections being safe and efficacious. Overall, the risk of urinary retention was around 6% across the study populations. Keywords: urgency urinary incontinence, urinary retention, nocturia, frequency